1977
DOI: 10.1002/ijc.2910190508
|View full text |Cite
|
Sign up to set email alerts
|

Morphological transformation of early passage Golden Syrian Hamster embryo cells derived from cryopreserved primary cultures as a reliable in vitro bioassay for identifying diverse carcinogens

Abstract: Cryopreserved primary cultures of golden Syrian hamster embryo cells were used as the source of target and feeder cells for establishing an in vitro carcinogenesis bioassay. The primary culture giving the best overall response in a pretest before freezing gave positive results in 20 consecutive experiments when retested with 3-methylcholanthrene after cryopreservation, indicating that pretested cryopreserved cultures can serve as a source of susceptible target cells in an in vitro carcinogenesis bioassay. Simi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
58
0
1

Year Published

1981
1981
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 310 publications
(63 citation statements)
references
References 11 publications
3
58
0
1
Order By: Relevance
“…Many short-term in vitro assays for its genotoxicity gave negative results (Andrews et al, 1980;Pienta et al, 1977;lype et al, 1982;Probst & Neil, 1980;McQueen & Williams, 1981) except for the report by Althaus et al (1982) who demonstrated that treatment of primary cultures of rat hepatocytes with MPH stimulated DNA repair synthesis and caused the formation of alkali-labile lesions in hepatocellular DNA. Evidence for the covalent binding of MPH or its metabolites to cellular DNA is lacking (Lijinsky & Muschik, 1982).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many short-term in vitro assays for its genotoxicity gave negative results (Andrews et al, 1980;Pienta et al, 1977;lype et al, 1982;Probst & Neil, 1980;McQueen & Williams, 1981) except for the report by Althaus et al (1982) who demonstrated that treatment of primary cultures of rat hepatocytes with MPH stimulated DNA repair synthesis and caused the formation of alkali-labile lesions in hepatocellular DNA. Evidence for the covalent binding of MPH or its metabolites to cellular DNA is lacking (Lijinsky & Muschik, 1982).…”
Section: Discussionmentioning
confidence: 99%
“…In short term in vivo animal studies, MPH acts as a promoter of the induction of enzyme altered foci and hepatomas in the liver of carcinogen initiated rats, but a single injection of MPH was ineffective in inducing foci in the liver when followed by a liver tumour promoter (Couri et al, 1982;Furuya et al, 1983). In several in vitro carcinogenicity tests such as the Salmonella mutagenesis test, the transformation assays with hamster embryo cells and the quantitation of induction of sister chromatid exchanges, MPH yielded negative results (Andrews et al, 1980;Pienta et al, 1977; lype et al, 1982). Although earlier reports indicated that MPH was ineffective in inducing DNA repair synthesis in cultured rat hepatocytes (Probst & Neil, 1980;McQueen & Williams, 1981), positive results were reported more recently (Althaus et al, 1982).…”
mentioning
confidence: 99%
“…Ni3S2 also enhanced the carcinogenic effects of benzo(a)pyrene (122) and 20-methylcholanthrene in experimental animals (123). In vitro mammalian cell tests demonstrate that Ni3S2 and NiSO4 compounds give rise to mammalian cell transformation (124)(125)(126)(127)(128)(129)(130).…”
Section: Nickelmentioning
confidence: 99%
“…For example, the frequency of spontaneous type II or type III foci in the C3H1OT1/2 cell transformation assay has been either low or undetectable (1)(2)(3)(4)(5). Similarly, many laboratories have not reported spontaneous transformed colonies of Syrian hamster embryo (SHE) cells in the SHE colony transformation assay (6,7); however, other laboratories report background activities for this assay (8). In contrast, spontaneous transformation has been routinely detected in both the BALB/c-3T3 (9)(10)(11)(12)(13) and Simian adenovirus 7/SHE (SHE/SA7) transformation assays (14)(15)(16).…”
Section: Introductionmentioning
confidence: 99%